The Effect of Using Interactive Games (Gamestolearnenglish.com) on Eleventh Graders’ English Vocabulary Mastery at an Agricultural Vocational School - Luluk Juan Pertiwi (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2026)
This study explores the impact of interactive games on the English vocabulary mastery of grade XI Animal Nursing students at the Kupang State Agricultural Vocational School. Given the low level of vocabulary mastery in vocational high school students, the study aims to investigate how using Gamestolearnenglish.com, an interactive game-based platform, can enhance vocabulary skills. A quasi-experimental design with pre- and post-treatment assessments was implemented. The results showed a significant improvement in students' vocabulary mastery, with the average score rising from 73.70 to 83.52, an increase of 9.82 points. The Shapiro-Wilk test confirmed the normality of the data, and a paired-sample t-test revealed a significant difference between the pre- and post-assessment (p = 0.000). This suggests that the use of interactive games significantly contributes to the enhancement of students' ability to recognize, understand, spell, and use vocabulary. These findings highlight the effectiveness of game-based learning in improving English vocabulary skills among vocational high school students, particularly in agricultural fields.